PEMBUATAN DAN KARAKTERISASI KATALIS TIO2/KARBON AKTIF DENGAN METODE SOLID STATE - Septiani, Upita; Gustiana, Mega; -, Safni (Universitas Andalas, 2015)
Composite catalyst of TiO2/Activated Carbon (TiO2/AC) had been synthesized with successfully by solid-state method. Synthesis was done by varying the addition of AC 5%, 10% and 15% of the mass of TiO2 was used. Composite catalyst was calcinated at temperature 400Â°C and characterized by Fourier Transform Infra-Red (FTIR), X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). FTIR spectrum show that the absorption appearedin the regionof C=C at wave number 1600-1800 cm-1, that assumed from AC. From XRD we can see that with variated of AC do not given different XRD patterns significantly, crystal structure of composite catalyst is anatase. SEM images showed that AC prevented the aglomeration of TiO2 that would expand surface area and increased catalytic activity of TiO2.